Ultra‐low loss 2‐core fibre for expanding submarine cable capacity - Takemi Hasegawa (IET Optoelectronics, 2024)
Abstract 2‐core fibre for submarine cable is becoming the first commercial application of multi‐core fibre, which should enable to expand the capacity beyond the current limitation of submarine cable size. For successful commercial applications of 2‐core fibre, it is important to minimise the complexities in manufacturing, splicing, and fibre handling. The 2‐core fibre design for minimum complexity is reviewed.